A global correlation of the step-wise consolidated crust-stripped gravity ﬁeld quantities with the topography, bathymetry, and the CRUST 2.0 Moho boundary - TENZER, Robert; HAMAYUN, K; VAJDA, Peter (Contributions to Geophysics and Geodesy, 2009)
We investigate globally the correlation of the step-wise  consolidated crust- stripped gravity ﬁeld quantities with  the topography, bathymetry, and the Moho bound- ary.   Global  correlations are  quantiﬁed in terms  of Pearson’s  correlation coeﬃcient. The elevation and bathymetry data  from the ETOPO5 are used to estimate the correlation of the gravity ﬁeld quantities with the topography and bathymetry. The 2×2 arc-deg discrete data  of the Moho depth from the global crustal model CRUST 2.0 are used to estimate the correlation of the gravity ﬁeld quantities with the Moho boundary. The results reveal that the topographically corrected gravity ﬁeld quantities have the highest  absolute correlation with the topography. The negative correlation of the topographically corrected gravity disturbances with  the topography over  the continents reaches –0.97.  The ocean,  ice and sediment density contrasts stripped and topographically corrected gravity ﬁeld quantities have  the highest  correlation with  the bathymetry (ocean  bottom  relief ).  The correlation of the ocean,  ice and  sediment density contrasts stripped and  topographically corrected gravity disturbances over  the oceans  reaches 0.93.  The consolidated crust-stripped grav- ity  ﬁeld  quantities have  the  highest  absolute correlation with  the  Moho boundary.  In particular, the global  correlation of the consolidated crust-stripped gravity disturbances with  the  Moho boundary is found  to be –0.92.  Among  all  the investigated gravity ﬁeld quantities, the  consolidated crust-stripped gravity disturbances are  thus  the best  suited for a reﬁnement of the Moho density interface by  means  of the gravimetric modeling  or inversion.